INFLUENCE ANALISYS OF MUDHARABAH, MUSHARAKAH, AND MURABAHAH FINANCING TO PROFITABILITY OF SHARIA COMMERCIAL BANK IN INDONESIA 2016-2019 WITH NON PERFORMING FINANCING AS INTERVENING VARIABLE - Aditama Dewantara; Anton Bawono (ISLAMICONOMIC: Jurnal Ekonomi Islam, 2020)
This study aims to determine the effect of mudharabah, musharakah, and murabahah financing on profitability through problem financing as a mediating variable. The examined data was sourced from the annual report of Islamic Banking Statistics published by the Otoritas Jasa Keuangan (OJK). The used analytical method is multiple regression and path analysis. The results of this study indicate that mudharabah, musharakah and murabahah financing do not have a significant effect on profitability directly. And then based on the path analysis stated that problematic financing can mediate the influence of musharakah financing on profitability, but it cannot mediate mudharabah and murabahah. The difference between this study with the others is the use of NPF as intervening variable wich is still rarely used by other researchers.